Development of the Third-trimester Pregnancy Knowledge Questionnaire (TPKQ): A Pilot Study - Nurul Jannah; Gunavathy Selvarajh (PT Inovasi Pratama Internasional, 2026)
Background: Maternal knowledge during the third trimester is critical for timely care-seeking and preparation for childbirth, yet standardized instruments specific to this phase remain limited. Objective: This study aimed to develop and pilot test the Third-trimester Pregnancy Knowledge Questionnaire (TPKQ). Methods: A methodological pilot study involved four experts and 110 third-trimester pregnant women. Items were derived from literature and organized into four dimensions: danger signs and care-seeking, birth preparation and delivery planning, preventive care before birth, and maternal conditions affecting labor outcomes. Content validity was assessed using Item and Scale Content Validity Indexes, response-based validity via corrected item–total correlations, and internal consistency with Cronbach’s alpha. Results: The TPKQ includes 10 multiple-choice items with dichotomous scoring. All items showed acceptable content validity (I-CVI = 0.75–1.00; S-CVI/Ave = 0.93), adequate discrimination (r = 0.36–0.46), and good reliability (α = 0.81). Dimension scores suggested higher knowledge of danger signs and lower knowledge of preventive care. Conclusion: The TPKQ demonstrates preliminary validity and reliability